Peroral video cholangioscopy to evaluate indeterminate bile duct lesions and preoperative mucosal cancerous extension: a prospective multicenter study - Osanai, M.; Itoi, T.; Igarashi, Y.; Tanaka, K.; Kida, M.; Maguchi, H.; Yasuda, K.; Okano, N.; Imaizumi, H.; Itokawa, F. (Endoscopy, 2013)
Background and study aims: Despite the development of peroral video cholangioscopy (PVCS), no prospective multicenter studies have been undertaken to investigate the diagnostic accuracy of PVCS in biliary tract diseases. Therefore, the aim of this study was to clarify the accuracy of PVCS in evaluating biliary tract lesions.Patients and methods: This study was a prospective multicenter study at five tertiary referral centers in Japan and included 87 eligible patients with biliary tract diseases who underwent PVCS. The study evaluated the ability of PVCS to diagnose indeterminate biliary tract diseases, detect mucosal cancerous extension preoperatively in extrahepatic bile duct cancers, and predict adverse events.Results: The use of PVCS appearance alone correctly distinguished benign from malignant indeterminate biliary lesions in 92.1 % of patients whereas biopsy alone was accurate in 85.7 %. In extrahepatic bile duct cancer, mucosal cancer extended histologically at least 20 mm in 34.7 % (17/49) of patients. The accuracy rate of PVCS to evaluate the presence or absence of mucosal cancerous extension by endoscopic retrograde cholangiography (ERC) alone, ERC with PVCS, and ERC with PVCS + biopsy were 73.5 %, 83.7 %, and 92.9 %, respectively.Adverse events were seen in 6.9 % of PVCS patients, but no serious complications were observed.Conclusion: PVCS enhanced the accurate diagnosis of biliary tract lesions by providing excellent resolution in combination with biopsy.